Factors limiting U.S. investment abroad : part 2, business views on the U.S. government's role - U.S. Department of Commerce; Bureau of Foreign Commerce (Washington, D.C. : U.S. Government Printing Office, 1954)
This analysis of the views of American businessmen concerning the role of the U.S. Government in private foreign investment is the second part of a report on a thorough study of impediments to private investment abroad and of means whereby these impediments can be removed or minimized.
osc 28/07/2016
Loans
Keywords: Foreign direct investment; United States